Hand eczema: prevalence and risk factors of hand eczema in a population of 2274 healthcare workers - Ibler, Kristina S.; Diepgen, Thomas L. (Contact dermatitis, 2012)
Background. Healthcare workers are at increased risk of developing hand eczema. Objectives. To investigate the prevalence and severity of self-reported hand eczema, and to relate the findings to demographic data, occupation, medical speciality, wards, shifts, and working hours. Patients/materials/methods. A survey of 3181 healthcare workers was performed. Data were analysed with logistic regression. Data on sick leave and notification to the authorities were obtained. Results. The response rate was 71% (2274 of 3181). The 1-year prevalence of hand eczema was 21%, and was positively associated with atopic dermatitis, younger age, male sex (male doctors), and working hours. Eighty nine per cent of subjects reported mild/moderate lesions. Atopic dermatitis was the only factor significantly related to severity. Sick leave was reported by 8% of subjects, and notification to the authorities by 12%. Conclusions. The 21% prevalence of hand eczema in healthcare workers is double the prevalence in the background population. Eleven per cent of hand eczema patients reported severe/very severe eczema. No significant differences were found between professions or medical specialities with respect to prevalence or severity, but cultural differences between professions with respect to coping with the eczema were significant. Atopic dermatitis was related to increased prevalence and severity, and preventive efforts should be made for healthcare workers with atopic dermatitis.
Gesehen am 19.11.2018